SURGICAL TACTICS FOR THE INFLOW VARICOTHROMOPHLEBITIS - V. I. Rysin; Ya. M. Popovich (Сучасні медичні технології)
Purpose of the study. To develop the surgical tactics for the inflow varicothrombophlebitis.